MODELS OF BEHAVIOR OF A GIRLFRIEND WHEN OVERCOMING THE PROBLEM OF UNSUCCESSFUL IMPLEMENTATION OF REPRODUCTIVE FUNCTION (Psychology Travelogs, 2025)
The article examines the psychological aspects of reproductive function in married couples and its impact on marital relationship quality, focusing on behavioral patterns in situations of unsuccessful conception attempts. Special attention is given to constructive and destructive interaction models, which shape couples’ responses to reproductive difficulties. Constructive models are based on mutual support, open communication, and joint problem-solving, strengthening relationships, while destructive models involve avoidance of conversation, mutual accusations, or emotional withdrawal, increasing tension and conflicts. The study explored emotional and physiological stress reactions and their connection to interpersonal relationship quality. Survey results showed that women mainly experience inwardly oriented emotions – anxiety, depressive states, guilt, sleep disturbances, and appetite changes – whereas men display outwardly expressed reactions such as irritability, tension, and conflicts. Social pressure and stigmatization from the environment were significant factors for both sexes, intensifying alienation and destabilizing interactions. These findings highlight the complex interplay between emotional, relational, and social factors in couples facing reproductive challenges. The article emphasizes that overcoming reproductive-related psychological difficulties depends on the type of couple interaction. Constructive roles, such as “communicator,” “mediator,” and “peacemaker,” foster open discussion of emotions, empathy, and compromise. Destructive roles – “initiator” with pressure, “blackmailer,” or “passive/silent” – increase conflict, stress, and alienation. The findings underline the need for practical recommendations to help couples manage psychological challenges, strengthen constructive interaction, and support psycho-emotional and physical well-being.
Keywords: reproductive function; marital relations; psychological difficulties; behavior models; emotional support